Efficacy and Cost-Effectiveness of Anti-VEGF for Treating Diabetic Retinopathy in the Indian Population - Pramanik S; Mondal LK; Paine SK; Jain S; Chowdhury S; Ganguly U; Ghosh S; Bose C; Bhattacharjee K; Bhaduri G (Clinical Ophthalmology, 2021)
Subhasish Pramanik,1 Lakshmi Kanta Mondal,2 Suman Kalyan Paine,3 Sneha Jain,2 Subhankar Chowdhury,1 Upasana Ganguly,4 Sayantan Ghosh,2 Chiranjit Bose,1 Koena Bhattacharjee,2 Gautam Bhaduri5 1Institute of Post Graduate Medical Education and Research (IPGMER), Kolkata, 700020, India; 2Regional Institute of Ophthalmology (RIO), Medical College and Hospital, Kolkata, 700073, India; 3National Institute of Biomedical Genomics (NIBMG), Kalyani, West Bengal, India; 4Maharishi Markandeshwar Institute of Medical Sciences and Research, Mullana, Haryana, India; 5MGM Medical College, Kishanganj, Bihar, IndiaCorrespondence: Lakshmi Kanta MondalRegional Institute of Ophthalmology, Medical College, Kolkata, IndiaTel +91 9830830216Email Lakshmi.mondal62@gmail.comPurpose: In the present study, we aimed to evaluate the efficacy, safety, and cost-effectiveness of the anti-vascular endothelial growth factor (anti-VEGF), namely ranibizumab (RBZ) or bevacizumab (BVZ), after either focal or grid or scatter laser photocoagulation, for the treatment of diabetic macular edema (DME) in the Indian population.Methods: Retrospective data were collected in the Regional Institute of Ophthalmology, Kolkata, India between January 2018 and June 2019. Seventy-seven eyes received 3 consecutive monthly intravitreal injections of RBZ (0.5 mg) and were followed by prompt laser photocoagulation (within 7– 10 days after the third injection). Similarly, 51 eyes received 3 consecutive monthly intravitreal injections of BVZ (1.25 mg), an off-label drug, and were followed by prompt laser therapy. Safety assessments of the therapy, as well as surrogate markers of biochemical derangements related to diabetic retinopathy (DR), were also investigated at the end of 12 months.Results: Seventy-seven subjects who were given a treatment of RBZ+laser therapy showed average 6.87± 5.53 letters gain in their best-corrected visual acuity (BCVA) score, whereas the ones treated with off-label BVZ+ laser therapy demonstrated improvement in BCVA of an average 6.82± 5.76 letters in “Early Treatment Diabetic Retinopathy Study” (ETDRS) chart. The study also highlights the cost-effectiveness of both RBZ+laser and BVZ+laser therapies for the treatment of DME in DR. The results demonstrated that a subject has to pay 20.951 times more cost (in INR) for RBZ+laser therapy compared to BVZ+laser therapy, to get an almost similar outcome.Conclusion: BVZ is found to be the more attractive option for treating DME in DR for its cost-friendliness over RBZ in terms of BCVA outcome, as well as the safety perspectives, at least for the economically backward population in developing countries, like India.Keywords: diabetic retinopathy, diabetic macular edema, ranibizumab, bevacizumab, laser therapy, cost-effectiveness